19.4k views
2 votes
Make x the subject of the formula
6(a – cx) = 24​

User Stillenat
by
5.1k points

1 Answer

3 votes

Answer:

x = (a-4)/c

Explanation:

1) Multiply 6 for a and -cx

6a - 6cx = 24

2) Add -6a at the two members

-6cx + 6a -6a = 24-6a

-6cx = 24 -6a

3) Multiply the two members by -1

6cx = 6a - 24

4) divide the two members by 6c (assuming that its values is not 0)

x = (6a-24)/6c

5) simplify the second member

x = [6(a-4)]/6c

x = (a-4)/c

User Regularjoe
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.